Spiritual intelligence, spiritual health and occupational stress in Islamic organisations - Aini, Qurratul (HTS teologiese studies, 2023)
By reaching perfection and closeness to God and reaching the source of the light of existence, man can benefit from his endless mercy. Almighty God is absolute perfection, and nearness to absolute perfection is the main goal of creation. Considering that those who are not God do not have anything of their own, and whatever perfection God’s servants have is originally from God and belongs to him, the closer people get to God, the more they will benefit from God’s mercy. Therefore, in the work environment, this perfection appears in the form of spiritual intelligence and spiritual health based on Islamic teachings and affects organisational variables such as occupational stress. Today, the role of spiritual intelligence is considered an important issue in improving spiritual health, reducing occupational stress and effective social functioning, especially in an Islamic environment, which leads to a better understanding of employees about their job. Therefore, the present study aims to evaluate the effect of spiritual intelligence of Muslim managers on the spiritual health and occupational stress of employees in Islamic organisations in Iraq. The statistical population includes 3422 Muslim managers and employees of 50 service organisations (including finance, education and tourism) in Iraq in 2022. The results of the hypothesis test in Linear Structural Relations (LISREL) shows, spiritual intelligence has a significant effect on spiritual health (P = 0.885; T = 11.058). On the other hand, spiritual intelligence has a negative and significant effect on occupational stress (P = -0.763; T = -7.854). Finally, spiritual health also has a negative and significant effect on occupational stress (P = -0.912; T = -10.134).Contribution: The findings of the research indicate that spiritual intelligence leads to the improvement of spiritual health and as a result reduces occupational stress, especially in an Islamic environment. Therefore, it should be taken into consideration by the managers of the organisations in order to achieve the maximum benefit in light of Islamic teachings.